Analysis of the Implementation of the Independent Curriculum for IPAS Subject in Class IV-A at State Elementary School Tengah 03 - Yansah, Eka Adi; Zulfadewina, Zulfadewina (Journal of Social Science and Education Research, 2024)
This study evaluates the implementation of the Independent Curriculum at SDN Tengah 03, East Jakarta, a pilot school for this new curriculum. The aim is to assess the effectiveness of the curriculum in meeting students' learning needs and its application within the school environment. A qualitative approach with descriptive techniques was employed, including observation, interviews, and documentation. The research found that the Independent Curriculum focuses on exploring students' interests and talents, and the formation of the Pancasila Student Profile through integration into school culture and learning activities. While the curriculum provides greater learning freedom, weaknesses were identified in the IPAS teaching module that require improvement. The study recommends adjustments to the module to better align with students' interests and talents. The findings suggest that the Independent Curriculum is expected to enhance educational quality and produce more creative and character-driven students.